Prisão, tráfico e maternidade: um estudo sobre mulheres encarceradas - França, Marlene Helena de Oliveira (2013)
This research deals with the thematic relative questions to, the arrest, violence, traffic and maternity involving jailed women of the Center of Ressocialização Júlia Maranhão. For the unfolding of this study the workmanships of Brazilian authors had been used who are references in this area: Julita Lemgruber (1983); Iara Ilgenfritz and Bárbara M. To sound (2002). Soon, in this research it was necessary to articulate some agreements until it was possible to identify that to the relations imprisoned/institution; arrest/violence; canine tooth/maternity - even so of extreme relevance - does not give account to represent the feminine penitentiary Júlia given Maranhão its complexity: a convivência place, but also, of conflicts, where practical coercitive there the gifts, are legitimated for the society in general. One of the hypotheses of the study consists of the affirmation of that the question of the violence is a present element since early in the trajectory of life of these women, becoming determinative for its insertion in the life of the crime. Searching to describe the experiences of these women concerning the maternity, mainly to those involved ones in the traffic crime, it was opted to the use of interviews, with focus in the life history. From the stories of 37 interviewed mothers one evidenced that the speech on the maternity is a social construction of sort. The manifestation of the love of these mothers for its children suffers the influence from its concrete experiences while children and the relation that had been able - or not - to construct with its children before the imprisonment. The results of the study indicate that the violence cycles, gifts in the trajectory of life of the imprisoned women exert influence in the formation of its identity, making to assume that it over all has a relation between the violent standard and the practical one of crime, of the traffic crime. The study it also points the existence of a correspondence does not enter the Express in the legal and normative instruments that guide the institucional actions and the reality lived deeply for the woman-mother-female prisoner, becoming necessary the formularization and implementation of specific public politics for such reality, as form to minimize the impact that the capture provokes in the life of these women. It is concluded that a series of changes in the prisional system becomes necessary, in order to guarantee the right to the mothers to exert its maternity, in view of, over all, that the proximity with the children is factor of mental health and stimulaton in the process of social reinserção.